Description of How to Brushing teeth Against Ohi-s Status in Pannara Primary Student, Manggala District Makassar City - Usman, Faradillah (Jurnal Ilmiah Amanah Akademika, 2023)
Abstract. Dental and oral health is an indicator of overall health, well-being and quality of life. This condition is considered very important because problems with the teeth and mouth can limit an individual's capacity to bite, chew, smile, speak, and psychosocial well-being. The purpose of the study was to determine the picture of knowledge on how to brush teeth on OHI-S status in grade IV and V students at SD Inpres Pannara, Manggala District. This type of research is descriptive with a cross sectional design. The population of all grade IV and V students at SD Inpres Pannara, Manggala District, Makassar City is 50 people. The sampling technique in the study was purposive sampling. The results of the study were found that 32 people had a good level of knowledge (62%), 19 moderate (38%), and bad (0%). Dental and oral hygiene index of 3 people improved good hygiene (6%), 41 people had moderate hygiene (82%) and 6 people had poor hygiene (12%). The conclusion is that for knowledge, good results are obtained while OHI-S is included in the medium criteria.